Surgical Resection of Anastomotic Stenosis after Rectal Cancer Surgery Using a Circular Stapler and Colostomy with Double Orifice. (12th May 2019) - Imagami, Toru; Takayama, Satoru; Maeda, Yohei; Hattori, Taku; Matsui, Ryohei; Sakamoto, Masaki; Kani, Hisanori
Abstract : The double stapling technique has greatly facilitated intestinal reconstruction, particularly for anastomosis after anterior resection. However, anastomotic stenosis may occur, which sometimes requires surgical treatment. Redo surgery with reresection and reanastomosis presents a high risk of complications. Treatment methods need to be selected depending on the degree and location of stenosis. In an effort to propose a new resolution, reporting new cases and sharing valid experiences are necessary. An 82-year-old man diagnosed with rectal cancer had undergone laparoscopic anterior resection. Endoscopic balloon dilation performed for anastomotic stenosis had failed. Therefore, colostomy with double orifice was constructed on the oral side at 10 cm from the stenosis. Approaching from the anal and stoma side, the anastomotic stenosis was resected using a circular stapler. The colostomy was closed 1 month after surgery. Stenosis resection using a circular stapler requires the following steps: (1) passing the center shaft through the stenosis, (2) inserting the anvil head into the oral side of the stenosis, and (3) attaching the anvil head to the center shaft. This method can resect the stenosis using a circular stapler without being affected by postoperative adhesion in the pelvis. Compared to endoscopic balloon dilation, resection of the stricture by the circular stapler is thought to be reliable. This technique is particularly effective for localized stenosis, including anastomotic stenosis. It is considered that this method is minimally invasive and is low risk for complications. This method can contribute to the useful surgical option for refractory anastomotic stenosis after anterior resection.